2019
DOI: 10.5430/ijhe.v9n2p63
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards Engineering Ethical Issues: A Comparative Study between Malaysian and Indonesian Engineering Undergraduates

Abstract: This investigation reports the outcomes of a comparative study on attitude towards engineering ethical issues between engineering undergraduates of Malaysia and Indonesia. The study was conducted involving 83 Malaysian and 135 Indonesian undergraduates who pursuing their study in engineering programmes. A quantitative method was used in which  a questionnaire was administrated to elicit relevant data. The results of the data analysis showed that the attitude towards engineering ethical issues among Indonesian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…There are different ethical theories related to engineering ethics, and the most common ethical theories are utilitarianism, deontology, care and virtue ethics (Balakrishnan et al ., 2020). Utilitarianism is consequentialism, and its primary focus is to maximize utility; it is expressed in terms of pleasure or happiness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are different ethical theories related to engineering ethics, and the most common ethical theories are utilitarianism, deontology, care and virtue ethics (Balakrishnan et al ., 2020). Utilitarianism is consequentialism, and its primary focus is to maximize utility; it is expressed in terms of pleasure or happiness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was not a discussion relating to punishment or sanctions, which is the policy in academic institutions (Merkel, 2021). It seems that the pedagogy used in these courses had a positive effect on the students' attitude towards ethical issues, which is crucial for professional development of morality among pre-service teachers (Balakrishnan et al, 2020). Completing university education that focuses on acquiring large quantities of knowledge does not suffice for making proper decisions on a personal and social level.…”
Section: Alternative Assessment and Responsible Decision-makingmentioning
confidence: 99%
“…The engagement of UBs is of great risk to both development and various professionals in Ghana. Balakrishnan et al (2020) observed that practitioners often support themselves, giving rise to a feeling of rage and hatred at the detriment of others. It can be noted that political systems in Ghana, play a critical role in fuelling UPs in the construction industry.…”
Section: Unethical Behavioursmentioning
confidence: 99%